Screening and Optimization of Alkaline Protease Productivity from Bacillus sp. Agt from Tannery Effluent - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Bacillus sp. AGT strains was isolated from tannery effluent were optimized with respect to temperature, pH and incubation time, different carbon sources, different nitrogen sources and also it was optimized with respect to different agro industrial waste. Substantial level of protease enzyme activity for Bacillus sp. AGT isolate was achieved at 40Â°C, pH 9.0 during 18 hours incubation in our production medium containing maltose as carbon source and 0.5% gelatine as nitrogen source.